2015
DOI: 10.1002/ardp.201500178
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tolmetin Hydrazide–Hydrazones and Discovery of a Potent Apoptosis Inducer in Colon Cancer Cells

Abstract: Tolmetin hydrazide and a novel series of tolmetin hydrazide-hydrazones 4a-l were synthesized in this study. The structures of the new compounds were determined by spectral (FT-IR, (1)H NMR) methods. N'-[(2,6-Dichlorophenyl)methylidene]-2-[1-methyl-5-(4-methylbenzoyl)-1H-pyrrol-2-yl]acetohydrazide (4g) was evaluated in vitro using the MTT colorimetric method against the colon cancer cell lines HCT-116 (ATCC, CCL-247) and HT-29 (ATCC, HTB-38) to determine growth inhibition and cell viability at different doses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…As well as other NSAIDs, naproxen was reported to be efficient in the prevention of many cancers [3][4][5]. Hydrazide-hydrazones [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and 1,2,4-triazole rings [22][23][24][25][26] have diverse biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…As well as other NSAIDs, naproxen was reported to be efficient in the prevention of many cancers [3][4][5]. Hydrazide-hydrazones [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and 1,2,4-triazole rings [22][23][24][25][26] have diverse biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…13 C-NMR spectrum data of compound 4d 16 C-NMR spectrum data of compound 4d The results revealed that tolmetin hydrazone showed anticancer activity againts HT-29 colon cancer cell line (dose depended) with IC 50 value of 76 µM. Tolmetin hydrazone was then used in further tests to investigate the apoptotic effect on HT-29 cancer cell line.…”
Section: Figmentioning
confidence: 99%
“…Metastat (Col-3), minocyclin and doxycycline are the examples of these inhibitors (34). Küçükgüzel and co-workers (16) synthesized N'-[(2,6-dichlorophenyl)methyliden]-2-[1-methyl-5-(4-methylbenzoyl)-1H-pyrrol-2-yl]acetohydrazide and found activity againts HT-29 colon cancer cell line with IC 50 value of 76 µM. This information showed, against colon cancer cell line anticancer activiy of tolmetin maintains whereas the thiosemicarbazide molecule from the same compound have no activity againts colon cancer, instead, it shows activity againts prostate cancer cells.…”
Section: Figmentioning
confidence: 99%
“…Briely, cells were seeded into 96-well plates (10 4 cells/well) and incubated at 37°C in CO 2 incubator for 24 h. The next day, appropriate doses of drug were added and cells were further incubated for 24 or 48 h. MTT of 10 μL was added to each well for an additional 4 h. The precipitated formazan was dissolved in 100 μL of 10% SDS, and the absorbance was taken at 570 nm [38].…”
Section: Cell Viability Assaymentioning
confidence: 99%